Impact on heat rate and subsequent emissions due to varying operation of coal fired power plants - Akpan, Patrick Udeme-Obong (Department of Mechanical Engineering, 2020)
Energy mix modellers often use a constant emissions factor model, which more or less implies a constant heat rate, when trying to show the emissions reduction benefits of integrating renewable power generation system on the grid. This approach does not consider the fact that there is a deterioration in the heat rate with load for the Coal Fired Power Plants that need to accommodate the additional renewable supply. If varying heat rate were to be included in a study, it is often limited to plant specific cases. This PhD presents a novel Variable Turbine Cycle Heat Rate (V-TCHR) model for predicting the part load Turbine cycle heat rate (TCHR) response of various Coal Fired Power Plant (CFPP) architectures, without detail knowledge of the entire steam cycle parameters. A total of 192 process models of representative CFPP architectures were developed using a Virtual Plant software. The models had different combinations of the degree of reheat; the throttle temperature; throttle pressure; and condenser cooling technology. The part load response of all the models were simulated using the software.